ANALYSIS OF THE CONTINUITY BETWEEN THE CONTENT OF PHYSICAL EDUCATION IN PRIMARY GRADES AND PRESCHOOL EDUCATION PROGRAMS - Usmonov Zohidjon Normatovich (Bright Mind Publishing, 2026)
This article provides a scientific and pedagogical analysis of the content of physical education in primary grades and its continuity with preschool education programs. The study substantiates the importance of the principle of continuity between educational stages in ensuring children’s physical development. Particular attention is paid to the consistent development of basic motor skills and physical qualities formed in preschool institutions within physical education classes at the primary school level. A comparative analysis of curricula was conducted, identifying both harmonized and inconsistent aspects of their content. The research findings serve as a basis for developing practical recommendations aimed at improving the content of physical education in primary grades, organizing classes in accordance with age-specific characteristics, and ensuring methodological consistency between educational stages.
Keywords: Healthy lifestyle, motor skills, physical education, physical qualities, sport, continuity.